UPAYA PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MELALUI PENDEKATAN CULTURALLY RESPONSIVE TEACHING SISWA KELAS IV SD INPRES 1 TATURA - Indriyani Nur; Azizah; Hermin (STKIP Subang, 2025)
This classroom action research sought to elevate Indonesian language learning achievements by integrating the Culturally Responsive Teaching (CRT) approach among fourth-grade students at SD Negeri 1 Tatura. The study engaged 20 learners, including 8 boys and 12 girls, as the main subjects of observation. Data collection employed learning outcome tests carefully crafted to evaluate students’ grasp of the material. Results indicated a notable progression in learning mastery, beginning at 45% during the pre-action phase, rising to 70% in Cycle I, and ultimately reaching 85% in Cycle II. Consequently, it can be inferred that the implementation of CRT substantially contributes to enhancing Indonesian language learning outcomes for fourth-grade students at SD Negeri 1 Tatura.